Introgression and adaptive potential following heavy bleaching events in Acropora corals - Furukawa, Mao; Tarigan, Ariyo Imanuel; Kitanobo, Seiya; Hanahara, Nozomi; Ohki, Shun; Morita, Masaya (Current biology, 2025)
The decline of reef-building corals due to severe bleaching events poses a global threat to coral reef ecosystems. In Okinawa, Japan, despite the devastating 1998 bleaching event and subsequent elevated sea surface temperatures in summer, three interbreeding coral species within the Acropora cf. humilis group (A. cf. gemmifera, A. cf. humilis, and A. cf. monticulosa) demonstrated remarkable recovery after the heavy bleaching event in 1998. To investigate the role of genetic introgression in coral adaptation, we analyzed hybrid reproduction, morphology, and genomic data from these species. Our findings revealed natural hybrids between the species, with morphological traits such as robust branches in F2 hybrids. Hybrids also produced gametes compatible with those of the parental species, supporting the occurrence of backcrossing, leading to introgression among the A. cf. humilis group. Genetic diversity, represented by expected heterozygosity (He) and inbreeding coefficients (F), further suggests admixture among A. cf. humilis species. Demographic analyses indicate hybridization occurred within five generations (∼25 years), potentially after the bleaching event in 1998. Additionally, we identified outlier genomic regions predicted to be under selection, including coding sequences with potential roles in thermal tolerance or stress response. These findings implicate introgression among the A. cf. humilis group as a mechanism contributing to coral survival under environmental stress, such as higher water temperatures in the summer. By integrating analyses of hybrid morphology, reproductive compatibility, genetic diversity, and introgression, our study underscores the critical role of hybridization among the interbreeding species in stabilizing coral reef ecosystems and responding to climate-change-induced challenges. [Display omitted] •Heavy bleaching events are linked to introgression among the Acropora humilis group•Hybrids produce gametes compatible with parental species, supporting hybridization•Hybrids exhibit distinct morphology that may have advantages in specific environments•Introgression boosts genetic diversity and may enhance coral heat stress tolerance Furukawa et al. show that hybridization among three Acropora species in Okinawa may contribute to coral recovery after the 1998 bleaching event. Morphological, reproductive, and genomic analyses reveal recent introgression and candidate genes under selection related to thermal stress.